Membrane fatty acid desaturase: biosynthesis, mechanism, and architecture - Abd Halim, Nur Farah Anis; Mohamad Ali, Mohd Shukuri; Thean, Adam Chor Leow; Raja Abd Rahman, Raja Noor Zaliha (Springer, 2022)
Fatty acid desaturase catalyzes the desaturation reactions by inserting double bonds into the fatty acyl chain, producing unsaturated fatty acids, which play a vital part in the synthesis of polyunsaturated fatty acids. Though soluble fatty acid desaturases have been described extensively in advanced organisms, there are very limited studies of membrane fatty acid desaturases due to their difficulties in producing a sufficient amount of recombinant desaturases. However, the advancement of technology has shown substantial progress towards the development of elucidating crystal structures of membrane fatty acid desaturase, thus, allowing modification of structure to be manipulated. Understanding the structure, mechanism, and biosynthesis of fatty acid desaturase lay a foundation for the potential production of various strategies associated with alteration and modifications of polyunsaturated fatty acids. This manuscript presents the current state of knowledge and understanding about the structure, mechanisms, and biosynthesis of fatty acid desaturase. In addition, the role of unsaturated fatty acid desaturases in health and diseases is also encompassed. This will be useful in understanding the molecular basis and structural protein of fatty acid desaturase that are significant for the advancement of therapeutic strategies associated with the improvement of health status.